The Gut Microbiome Is Associated with Clinical Response to Anti-PD-1/PD-L1 Immunotherapy in Gastrointestinal Cancer - Peng, Zhi; Cheng, Siyuan; Kou, Yan; Wang, Ziqi; Jin, Rong; Hu, Han; Zhang, Xiaotian; Gong, Ji-Fang; Li, Jian; Lu, Ming; Wang, Xicheng; Zhou, Jun; et al. (Cancer immunology research, 2020)
We report on a comprehensive analysis of the gut microbiomes of patients with gastrointestinal (GI) cancer receiving anti-PD-1/PD-L1 treatment. The human gut microbiota has been associated with clinical responses to anti-PD-1/PD-L1 immunotherapy in melanoma, non-small cell lung cancer, and renal cell carcinoma. We aimed to investigate this association in GI cancers. We also identified bacterial taxa with patient stratification potential. We recruited 74 patients with advanced-stage GI cancer receiving anti-PD-1/PD-L1 treatment and collected their fecal samples prior to and during immunotherapy, along with clinical evaluations. Our 16S rRNA taxonomy survey on the fecal samples revealed an elevation of the / ratio in patients, with a preferred response to anti-PD-1/PD-L1 treatment, and a particular subgroup of responders harboring a significantly higher abundance of , and The shotgun metagenomes of the same samples showed that patients exhibiting different responses had differential abundance of pathways related to nucleoside and nucleotide biosynthesis, lipid biosynthesis, sugar metabolism, and fermentation to short-chain fatty acids (SCFA). Gut bacteria that were capable of SCFA production, including , and , were positively associated with anti-PD-1/PD-L1 response across different GI cancer types. We further demonstrated that the identified bacterial taxa were predictive of patient stratification in both our cohort and melanoma patients from two previously published studies. Our results thus highlight the impact of gut microbiomes on anti-PD-1/PD-L1 outcomes, at least in a subset of patients with GI cancer, and suggest the potential of the microbiome as a marker for immune-checkpoint blockade responses. .